Integration of Religion and Science: Thoughts of Kh. Ahmad Dahlan in Islamic Education Reform in Indonesia - Mutaqin, Dadang Zenal; Wulandari, Fitri; Nursilah, Nina; Nurjanah, Sinta; Aisah, Siti (UNIVERSITAS PAKUAN, 2025)
KH. Ahmad Dahlan, a reformer of Islamic education in Indonesia, integrated religious values with modern knowledge to address educational challenges during the colonial era. Through the establishment of Muhammadiyah in 1912, he combined religious teachings with general subjects such as science, mathematics, and languages in a modern educational system. Madrasah Mu'allimin Muhammadiyah exemplified his vision of holistic education. This study employs a qualitative method with a historical-descriptive approach, examining KH. Ahmad Dahlan's thoughts and contributions to educational reform. Thematic analysis reveals the relevance of his ideas in shaping Muslim individuals who are faithful, knowledgeable, and competitive in the modern world. His legacy remains a cornerstone of Islamic education development in Indonesia.